Soil alterations by chronosequence of pastures in crop-livestock-forestry systems - Oliveira, Geslanny Oliveira Sousa; Damacena, Jossimara Ferreira; Oliveira, Pedro Luid de Sousa; Muniz, Luciano Cavalcante; Sousa, Maria Karoline de Carvalho Rodrigues de (Scientia Agraria Paranaensis, 2022)
The intensive use of land has accelerated the loss of soil quality, a process that can be avoided by adopting conservationist production systems, such as the Integrated Crop-Livestock-Forest (CLFI system). It is noteworthy that in the Southwest of the State of Maranhão a substantial portion of soils in rural properties are degraded and in distinct stages of erosion, since they have been exploited for decades with non-properly managed pastures. Therefore, the objective of this work was to emphasize the importance of physical and chemical changes in the soil of pastures under crop-livestock-forest integration in general and in the Amazon region of state of Maranhão, Brazil. Therefore, a literature review was conducted through a search for studies in the Google Scholar database, which encompasses multiple other databases, such as Scielo, Elsevier, Scopus, Capes, and others. In face of the conditions of degradation in pastures throughout the state of Maranhão and the broad distribution of native forests such as Babassu forests, the use of technology from CLFI systems could allow for their recovery and sustainable status by means of economically and ecologically feasible productivity. Research on this field is therefore necessary to highlight short- and long-term efficiencies regarding carbon sequestration and quality of organic matter on the soil.